Innovative Approaches to the Professional Preparation of Future School Leaders in the Field of Media Education - Qizi, Alimova Kunduz Oybek (EDUMALSYS Journal of Research in Education Management, 2025)
In the context of globalization, media education has emerged as a vital component of educational leadership, particularly in preparing future school administrators to navigate increasingly digital environments. This study aims to explore the core principles of media education, its defining features, and its function within contemporary educational management. Employing a qualitative research design supported by recent empirical data, the study examines how media education fosters essential digital competencies among aspiring school leaders, while simultaneously equipping them to safeguard students from the adverse effects of unregulated information exposure. Findings indicate that approximately 68% of adolescents spend 4–5 hours daily on the internet and social media, significantly influencing their social, cultural, and moral development. Moreover, around 45% of students report encountering harmful online content, with over 30% admitting to poor decision-making as a result of misinformation. These findings underscore the dual role of media education in promoting critical thinking and establishing a secure informational environment within schools. The study concludes that enhancing media literacy is essential not only for effective educational leadership but also for mitigating the risks posed by unchecked digital information. The research contributes to the discourse on educational policy and practice by emphasizing the integration of media literacy as a core competency in school leadership development programs.